1977
DOI: 10.1111/j.1600-051x.1977.tb01895.x
|View full text |Cite
|
Sign up to set email alerts
|

The plaque‐inhibiting effect of copper amalgam

Abstract: In order to assess whether copper amalgam accumulates less bacterial plaque than silver amalgam, 14 copper amalgam cervical restorations were placed in 10 patients. Control silver amalgam fillings were placed in homologous teeth of the same jaw. To evaluate the amount of plaque, the stained areas on the amalgams were analyzed from photographs with a planimetric method. Further quantitative analyses of plaque growth on copper amalgam were carried out with microbiological methods, for which a new group of 10 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Copper amalgam has also been shown to inhibit plaque formation in vivo (Hyppa & Paunio, 1977). However, recently it has been demonstrated that the new high copper amalgams have little or no inhibitory efl'ect on plaque samples in vitro (Heys et al, 1979).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Copper amalgam has also been shown to inhibit plaque formation in vivo (Hyppa & Paunio, 1977). However, recently it has been demonstrated that the new high copper amalgams have little or no inhibitory efl'ect on plaque samples in vitro (Heys et al, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…Previous in vitro work has found amalgam, especially copper amalgam, to be both cytotoxic (Lierskar, 1974;Takahashi, 1975) and bacteriostatic (McCue, McDougall & Shay, 1951;Shay, Allen & Martz, 1956). Copper amalgam has also been shown to inhibit plaque formation in vivo (Hyppa & Paunio, 1977). However, recently it has been demonstrated that the new high copper amalgams have little or no inhibitory efl'ect on plaque samples in vitro (Heys et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial properties of amalgam alloys have been attributed to combined effects of various bacteriotoxic elements re- leased by the alloys (10)(11)(12)(13). The concentrations of the bacteriotoxic elements (Ag, Hg, Cu) determined in the present sttidy after the 4-h experimental period were iow.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, to avoid excessive drilling of cavities in children's teeth, copper cements and filling materials have been used, which, by their bacteriostatic effect may limit caries. Bacterial growth around and underneath dental fillings is a constant problem and compared with other materials, those that contain copper have been shown to reduce bacterial growth and dental plaque formation (Turkheim 1953;Hyppa & Paunio 1977: Bundy et al 1980. Recent Scandinavian work has shown that copper sulphate mouth washes may be a better clinical alternative to chlorhexidine mouth washes in reducing the levels of dental plaque (Wiler & Rolla 1982).…”
Section: Discussionmentioning
confidence: 99%